We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
0
169
1
avatar+589 

Given f(x)=3x2+4x and g(x)=2x2−x+1 .

What is (f+g)(x) ?

 Feb 28, 2018
 #1
avatar+99736 
+2

 f(x)=3x^2+4x and g(x)=2x^2−x+1

 

(f + g)x  =

 

[  3x^2+4x ] +   [ 2x^2−x+1 ]     =

 

5x^2 + 3x + 1

 

cool cool cool

 Feb 28, 2018

25 Online Users

avatar
avatar